Analisis Faktor-Faktor Pengaruh Kinerja Keuangan dan Ukuran Perusahaan Terhadap Profitabilitas Bank : (Studi Kasus Pada PT. BANK DANAMON (Persero) Tbk. Periode 2012-2021) - Af Sari, Winda; Indiworo, Hawik Ervina; Violinda, Qristin (Jurnal Riset Rumpun Ilmu Ekonomi, 2024)
The purpose of this research is to find out what factors in financial performance influence the growth of profitability at Bank Danamon and to find out whether company size at Bank Danamon can affect the growth of profitability at Bank Danamon. In conducting this research, the researcher was guided by previous studies and the research method used in this method was quantitative research and for the validity of the data, the researcher took samples from the official Danamon bank financial reports that had been published and had been processed by the researcher. The results of the analysis in this study show that the Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), and company size have a significant positive influence on bank Danamon TBK's profitability, while Net Interest Margin (NIM) and BOPO have no effect on the profitability of bank Danamon Tbk.